Model polskiego rolnictwa – wobec aktualnych wyzwań - Ziętara, Wojciech (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2009)
In the paper tendencies of changes of factors of production prices in agriculture, agricultural products in the span of 1995–2007 as well as changes of parity farm area. As the result of faster growth rate of factors of production costs than agricultural prices, there occurs permanent increase of parity farm area. It causes deterioration of farmer’s income situation in comparison with working in non-agricultural branches. The main cause of deepen differences in the income situations of farmers is low mobility of labour factor in agriculture as well as land factor. Changes of the area of agricultural farms in Poland in comparison with chosen European countries were also presented. Against a background of that the model of Polish agriculture was presented